Conceptions of Quality of Pre-Service Teacher Education from Stakeholder Perspectives: A Case Study of a Vietnamese University (Journal of Contemporary Educational Policies and Practices, 2022)
This paper reports the findings of an investigation into pre-service teacher education (PTE) at a Vietnamese university. The qualitative case study focuses on the key stakeholders’ conceptions of the quality of pre-service teacher education in the provision of two social science departments at the selected university. The study draws on key policy documents and in-depth interviews within an interpretive paradigm based on a sample of policymakers, institutional leaders, academic staff, and students. The study reveals the conceptions of quality of PTE from the perspectives of governmental bodies to the perspectives of the front-liners in the PTE, which point to an emphasis on the notion of ‘quality as fitness for purpose’ and the classic model of ‘input-process-output quality’. The evidence suggests that while there is the stakeholders’ receptiveness to and compliance with the policy of standards in education, there is a lack of critical ideas about the professional standards for teachers. The study enriches the conceptual understanding of education quality, informing the development of policy and practice of teacher education in the context of Vietnam.
Keywords: Pre-service teacher education; quality; standards; stakeholders; Vietnamese education